RETRACTED: Upregulation of CCT-3 Induces Breast Cancer Cell Proliferation Through miR-223 Competition and Wnt/β-Catenin Signaling Pathway Activation - Qu, Hongbo; Zhu, Fang; Dong, Huaying; Hu, Xiongqiang; Han, Mingli (Frontiers in Oncology, 2020)
The clinical significance and function of Chaperonin containing TCP1 complex 3 (CCT-3) in breast cancer remains unknown. In this study, we found that CCT-3 was notably overexpressed in breast cancer tissues. Statistical analysis revealed a significant correlation of CCT-3 expression with advanced breast cancer clinical stage and poorer survival. Ablation of CCT-3 inhibited the proliferation and tumorigenicity of breast cancer cells in vitro and in vivo. CCT-3 may regulate breast cancer cell proliferation through a ceRNA network between miR-223 and β-catenin, thus affecting Wnt/β-catenin signaling pathway activation. We also validated CCT-3 and β-catenin is are novel direct targets of tumor suppressor miR-223. Our results suggests both mRNA and protein levels of CCT-3 are potential diagnosis biomarker and therapeutic target for breast cancer.